Quick Review of Seismic Behavior of Gravity Quay Wall. Issue 1 (February 2021) - Aldelfee, Alaa N.; Aldefae, Asad H.; Humaish, Wissam H.
Abstract: Earthquakes are one of the worst natural disasters that effect directly both human life and infrastructures around the world. The seismic behavior of a gravity quay wall has been outlined from art-of-literature in this review paper. Based on previous studies available on the subject, the paper includes a simplified introduction of gravity quay walls structures followed by the loads acting on the quay wall which are used in the design, modes of failure, forces generated during earthquakes, method of evaluation of displacement of gravity quay wall and the techniques that used to reduce the damage caused by liquefaction during earthquakes. Through the discussion, it was concluded that when shaking amplitude is high at low frequency and the soil of the foundation underneath the quay wall is loose, an increases in the distortion of the wall is noticed. Pore water pressure increasing in the soil and backfill soil leads to an increase in the amount of deformation twice the case of constant pore water pressure. The sliding of the caisson is greatly increased when liquefaction occurs in the backfill soil and the different used techniques to reduce the liquefaction damage during the earthquake had good results in several locations.